N,N'-Bis(4-chloro-phen-yl)urea. - Lo, K.M.; Ng, Seik Weng (International Union of Crystallography, 2008)
The carbonyl unit of the title compound, C(13)H(10)Cl(2)N(2)O, lies on a twofold rotation axis. The ring is aligned at 51.6 (1)° with respect to the N-C(=O)-N fragment. The two -NH- fragments of one mol-ecule form hydrogen bonds [2.845 (2) Å] to the C=O fragment of an adjacent mol-ecule, giving rise to the formation of a linear hydrogen-bonded chain.